Chemical nanoroughening of Ti40Nb surfaces and its effect on human mesenchymal stromal cell response. Issue 1 (11th July 2013) - Helth, A.; Gostin, P.F.; Oswald, S.; Wendrock, H.; Wolff, U.; Hempel, U.; Arnhold, S.; Calin, M.; Eckert, J.; Gebert, A.
Abstract Samples of low modulus beta‐type Ti40Nb and cp2‐Ti were chemically treated with 98% H2SO4 + 30% H2O2 (vol. ratio 1:1) solution. Surface analytical studies conducted with HR‐SEM, AFM, and XPS identified a characteristic nanoroughness of the alloy surface related with a network of nanopits of ∼25 nm diameter. This is very similar to that obtained for cp2‐Ti. The treatment enhances the oxide layer growth compared to mechanically ground states and causes a strong enrichment of Nb2O5 relative to TiO2 on the alloy surface. The in vitro analyses clearly indicated that the chemical treatment accelerates the adhesion and spreading of human mesenchymal stromal cells (hMSC), increases the metabolic activity, and the enzyme activity of tissue non‐specific alkaline phosphatase (TNAP). Surface structures which were generated mimic the cytoplasmic projections of the cells on the nanoscale. Those effects are more pronounced for the Ti40Nb alloy than for cp2‐Ti. The relation between alloy surface topography and chemistry and cell functions is discussed. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 31–41, 2014.